Strategies for coping with face-to-face oral communication problems employed by Thai University students majoring in English. - Surapa Somsai; Channarong Intaraprasert (Penerbit UKM, 2011)
Nowadays, it is undeniable that the communicative approach plays an important role in language teaching especially in the context where English is a foreign language and the ultimate goal of language teaching is to improve the communicative competence of language learners. Language learners can significantly improve their communicative competence by developing their ability to use communication strategies (CSs) or strategies for coping with face-to-face oral communication problems. The present study,which is exploratory in nature, primarily aimed at investigating how university students majoring in English for International Communication (EIC) cope with their face-to-face oral communication problems. The participants were 48 students studying at three different Rajamangala Universities of Technology in Thailand. A semi-structured interview was used for data collection. The obtained data were transcribed unfocusedly verbatim and translated from Thai into English. The translated data were then validated and analysed. Based on the role of the language learners when engaged in a conversation,i.e. as the message sender and as the message receiver, the results show two main categories of strategies for coping with face-to-face oral communication problems. The two groups of strategies employed for conveying a message to the interlocutor as the message sender: continuous interaction and discontinuous interaction subcategories and one group of strategies for understanding the message as the message receiver were reported.